Knowledge hubs for resilience in Vanuatu - Basil, Pauliane (Technical Centre for Agricultural and Rural Cooperation, 2018)
Natural disasters are a permanent feature in Vanuatu. Consequently, efforts to improve the resilience of farmers to natural disasters was seen as a priority by Live & Learn Vanuatu. Knowledge hub committees were put in place to help communities to improve their farming techniques. This knowledge hub approach was replicated across the country and, with government support, Pacific risk resilience workshops also took place.